2021
DOI: 10.3390/nu13020524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Supplementation in Early Life on Children’s Growth and Body Composition: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Vitamin D deficiency during pregnancy or infancy is associated with adverse growth in children. No systematic review has been conducted to summarize available evidence on the effect of vitamin D supplementation in pregnancy and infancy on growth and body composition in children. Objective: We aim to summarize the available evidence on the effect of vitamin D supplementation in pregnancy and infancy on child growth and body composition. Method: A systematic review and meta-analysis were performed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Supplementation with VD during pregnancy probably reduced the risks for preeclampsia, gestational diabetes, and babies with low birth weight at term. Another recent meta-analysis (3960 participants from 11 RCTs) found that VD supplementation was also associated with lower BMI and BMI z-score in children aged 3–6 years [ 147 ]. However, these data remain weak and the certainty level is only moderate, and so further large RCTs are needed to confirm these results.…”
Section: Maternal Vitamin D Deficiency and Links To Obesity And Adipo...mentioning
confidence: 99%
“…Supplementation with VD during pregnancy probably reduced the risks for preeclampsia, gestational diabetes, and babies with low birth weight at term. Another recent meta-analysis (3960 participants from 11 RCTs) found that VD supplementation was also associated with lower BMI and BMI z-score in children aged 3–6 years [ 147 ]. However, these data remain weak and the certainty level is only moderate, and so further large RCTs are needed to confirm these results.…”
Section: Maternal Vitamin D Deficiency and Links To Obesity And Adipo...mentioning
confidence: 99%
“…A systematic review and meta‐analysis of randomized controlled trials concluded that vitamin D supplementation during pregnancy or infancy may be associated with reduced adiposity in childhood. 48 The results showed that vitamin D supplementation during pregnancy or infancy was associated with increased length‐for‐age z‐score at 1 year of age, and lower BMI and BMI‐for‐age z‐score at 3–6 years of age. Although the results from these studies are not comparable with the current study, the results from MoBa overall agree with the results of the meta‐analysis.…”
Section: Discussionmentioning
confidence: 96%
“…However, none of the two classes identified in that study corresponded to the stable high class found in the current study. A systematic review and meta‐analysis of randomized controlled trials concluded that vitamin D supplementation during pregnancy or infancy may be associated with reduced adiposity in childhood 48 . The results showed that vitamin D supplementation during pregnancy or infancy was associated with increased length‐for‐age z‐score at 1 year of age, and lower BMI and BMI‐for‐age z‐score at 3–6 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Bi et al reported significantly greater height at 3 months, 9 months, and 12 months, but not at 6 months [ 82 ]. A meta-analysis from four clinical trials indicated that the LFA z-score was higher in infants at 1 year in the vitamin-D-supplemented group compared with the control [ 85 ]. Vitamin D supplementation at a higher dose and on an intermittent basis was found to be more beneficial than a lower dose (2000 IU) and daily or weekly supplement.…”
Section: Discussionmentioning
confidence: 99%